Relationship Between Attachment Styles, Childhood Trauma, and Psychotic Symptoms in Patients with Schizophrenia: Attachment Styles as a Mediating Role - Esra Bekircan; Şeyma Sehlikoğlu; Gülsüm Mine Çoban (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
This study was aimed at investigating the mediating role of attachment styles in the relationship between childhood trauma and positive and negative psychotic symptoms in patients with schizophrenia and determining the relationships between the variables. This descriptive, cross-sectional, and correlational study was conducted with 99 patients with schizophrenia who presented to the psychiatric outpatient clinic of a tertiary hospital between January 2025 and July 2025. Data were collected via face-to-face interviews using the Demographic and Clinical Characteristics Questionnaire, Childhood Trauma Questionnaire (CTQ), Relationship Scales Questionnaire (RSQ), and Positive and Negative Syndrome Scale (PANSS). There was a significant positive correlation between the scores obtained from the overall PANSS and CTQ by the patients with schizophrenia included in the study (r=0.260; p<0.01). There was a significant positive correlation between the PANSS and the Preoccupied Attachment subscale of the RSQ (r=0.309; p<0.01), and between the CTQ and the Avoidant Attachment Subscale of the RSQ (r=0.255; p=0.011). Attachment styles did not demonstrate a significant mediating effect in the relationship between childhood trauma scores and positive and negative symptoms. However, both the total effect and the direct effect were found to be statistically significant (B = 0.213, 95% CI [-0.009, 0.540], β = 0.048). A positive relationship was found between childhood trauma and positive and negative symptoms in patients with schizophrenia. It was also determined that there was a positive relationship between obsessive attachment and both positive and negative symptoms, and a positive relationship between dismissive attachment and childhood trauma.